BASHH 2018 UK national audit of HIV partner notification. (August 2021) - Bull, Lauren; Apea, Vanessa; Wiggins, Helen; Davies, Sophia; Saxon, Cara; Hughes, Amelia; Curtis, Hilary; Sullivan, Ann; ,
HIV partner notification (PN) is a highly effective strategy to identify people living with undiagnosed HIV infection. This national audit of HIV PN is against the 2015 British Association of Sexual Health and HIV (BASHH)/British HIV Association (BHIVA)/Society of Sexual Health Advisers (SHAA)/National AIDS Trust (NAT) HIV PN standards, developed in response to the 2013 BASHH/BHIVA national HIV PN audit. We report significant improvements in the number of contacts tested per index case, likely due, in part, to clearer definitions as well as better ascertainment and reporting. There remains scope for improvement with informing and testing contactable contacts. Recommendations from this audit include further refinement of definitions and development of a national proforma for HIV PN.